The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1128/aem.47.6.1195-1200.1984
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substrate Concentration and Organic and Inorganic Compounds on the Occurrence and Rate of Mineralization and Cometabolism

Abstract: Isopropyl N -phenylcarbamate (IPC) at 400 pg and 1 μg/ml was mineralized in samples of sewage, but only the lower concentration was mineralized in lake water samples in a 50-day period. IPC at 1 μg/ml disappeared from lake water, but it was converted to organic products. Mineralization of IPC at 400 pg/ml in lake water was enhanced by additions of inorganic nutrients or a mixture of nonchlorinated water pollutants but not by yeast extract or mixtures containing aromatic compounds or exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 21 publications
(18 reference statements)
2
19
1
Order By: Relevance
“…The same investigation showed that the acclimation period preceding PNP mineralization in lake water was markedly decreased when a mixture of several inorganic salts was added. The present study shows that the acclimation period for PNP mineralization was shortened by adding P, N, or S. A stimulation of biodegradation of organic chemicals in lake water by added inorganic nutrients, including P, N, Fe, and Mg, has been reported previously (la, [3][4][5]9). It is noteworthy that'the greatest effects noted in the present study were obtained at P concentrations much higher than those typically found in New York lakes, which usually range from 1 to 70 ,ug of P per liter (1).…”
supporting
confidence: 79%
“…The same investigation showed that the acclimation period preceding PNP mineralization in lake water was markedly decreased when a mixture of several inorganic salts was added. The present study shows that the acclimation period for PNP mineralization was shortened by adding P, N, or S. A stimulation of biodegradation of organic chemicals in lake water by added inorganic nutrients, including P, N, Fe, and Mg, has been reported previously (la, [3][4][5]9). It is noteworthy that'the greatest effects noted in the present study were obtained at P concentrations much higher than those typically found in New York lakes, which usually range from 1 to 70 ,ug of P per liter (1).…”
supporting
confidence: 79%
“…However, the present study provides data from the use of sediment: water microcosms for a comparative study of the effects of past chemical exposure and adaptation of sediment microbial populations on the mineralization rates of six PAHs in both estuarine and freshwater ecosystems. Since the degradation rate of PAHs may be affected by temperature [17,20] and exposure concentration [17,18], in this study these variables were held constant (22°C and 500 ng/g) to facilitate the comparison of PAH mineralization rates among ecosystems and different PAHs.…”
Section: Discussionmentioning
confidence: 99%
“…In a related study, Rubin et al (14) found the extent of mineralization of phenylacetate and p-nitrophenol to be greater in a eutrophic lake than in a mesotrophic lake. The effects of inorganic nutrients have been examined by workers in several laboratories (3,4,7,19). Dibble and Bartha (3) reported that mineral nutrient ratios of 60:1 (C/N) and 800:1 (C/P) resulted in the greatest amount of degradation of oil sludge on soil.…”
Section: Methodsmentioning
confidence: 99%